In vitro evaluation of synbiotics combinations of different inulin concentrations and multi-strains probiotics based on microbial growth and digestive enzymes production - AYMAN ALAMEEN MOHAMMED; SITI ASLAMYAH; ZAINUDDIN ZAINUDDIN; MUHAMMAD IQBAL DJAWAD (Society for Indonesian Biodiversity, 2024)
Abstract. Mohammed AA, Aslamyah S, Zainuddin, Djawad MI. 2024. In vitro evaluation of synbiotics combinations of different inulin concentrations and multi-strains probiotics based on microbial growth and digestive enzymes production. Biodiversitas 25: 3693-3702. This study aimed to isolate and characterize inulin from sweet potatoes, and to determine the best synbiotics combination between inulin and multi-strains probiotics (MSP) (Bacillus spp., Rhizopus sp., and Saccharomyces sp.) using an in vitro methods. In the first phase, inulin was extracted using two methods, namely rotary evaporator and freeze-dryer, and subsequently characterized through fourier transform infrared spectrometry (FT-IR). The results showed that freeze-dryer was more effective compared to evaporator method. In the second phase, an in vitro method was used to evaluate the effect of inulin concentrations (0, 1, 3, and 5 mL), type of medium (nutrient agar (NA), potato dextrose agar (PDA)), and incubation time (24 and 48 hours) on MSP growth by measuring microbial growth and digestive enzymes production. The results showed significant differences (P<0.05) in microbial growth based on inulin concentration and incubation time. Higher inulin concentrations led to increased growth of all probiotics strains compared to lower concentrations in both media. In addition, the 48-hour incubation time generally led to a higher microbial growth compared to 24 hours. The findings of this study also showed distinct patterns in the production of protease and amylase enzymes, with higher doses of inulin fostering protease production and lower doses being more conducive to amylase production.